Wholewheat bread: Effect of gradual water addition during kneading on dough and bread properties. (May 2021) - Parenti, Ottavia; Carini, Eleonora; Marchini, Mia; Tuccio, Maria Grazia; Guerrini, Lorenzo; Zanoni, Bruno
Abstract: Owing to the increasing demand for wholewheat flours (WWF) in bread-making, techniques are needed to improve WWF's poor technological properties and the resulting bread quality. We tested the effect of a common bakers' strategy to improve WWF performance: adding part of the water of the recipe during the kneading operation. First, the kneading operating conditions were optimized to perform the gradual water addition. The optimized dough sample was tested in a second trial to make an in-depth investigation of the effect of (i) the amount of water added during kneading and (ii) the total water content on dough molecular mobility (with Low Resolution 1 H NMR), dough rheology and bread quality. The gradual addition of water caused significant variations in proton mobility and dynamics; it improved dough rheological properties, but did not affect the bread quality. A higher dough water content (i.e., 60%) than predicted by the Farinograph test significantly improved the bread quality in terms of bread and crumb specific volumes, and bread texture. Combining the gradual water addition with high water content could be a strategy to enhance the quality of WWF doughs and breads, promoting the consumption of fibre-enriched foods. Highlights: The kneading operating conditions were optimized to perform the gradual water addition. Gradual water addition changed proton mobility and dynamics, and improved rheology. Water amounts higher than the Farinograph absorption value improved bread quality. Gradual water addition combined with high water amounts improved WWF bread-making.